(3YbO GdThGgO aj GdMce GdThGQOs - (3fLe GdOjf GdZRj , eMeO Hf eMeO Hf eMeO GdZRj GdYGeQj GdbQTj, fLe GdOjf CHh GdecGQe,J (B1061 (3g` s
(3ChdgG (B:s
(3hgd CMO dh TchJ Edjg Shi Gddg Lqd ojRjd GdqTcG s
(3BNQgG (B:s
(3hddg MeOj Ke GdUdGI Ydi GdeUWai NjQ Cgd GdJbi hCQLh ef Gddg oMSf GdNJGe dg GdMeO SHMGfg hGdKfG s
(3GdfSNI HgG MhGTs
(3hgj ebUhQJgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B288s
Keywords: (3GdCOHs